Novel cold-active amylase-producing bacterium from Chukchi Sea and its enzyme properties - Kim, Min Ju; Kim, Jin A; Park, Ha Ju; Yim, Joung Han; Kim, Il Chan; Han, Se Jong (Polish Polar Research, 2024)
A cold-active amylase was purified from Alteromonas sp. KS7913 isolated from the Chukchi Sea in the Arctic Ocean. After purification with use of ammonium sulfate precipitation, phenyl column chromatography, and size exclusion chromatography, 200.34 U mg−1 of purified amylase was obtained. The final yield was 3.4%, and the activity was 5.7-fold higher than that of the initial culture broth. KS7913 origin amylase showed a molecular weight of 70 kDa and optimal activity at 25°C, pH 7.0 in Tris-HCl buffer. The amylase was highly active, especially at 5°C, and maintained stability at basic conditions below 25°C. Copper and zinc ions inhibited enzyme activity, whereas manganese, barium, and calcium ions exhibited positive effects. This activity was maintained even in the presence of alcohol. The findings of this study supplement our understanding of cold-active amylases, and may have practical applications in low-temperature industries.